Optimization of Halal Certification Assistance for MSME Products at Pulau Merah Beach - Jauhariyah, Nur Anim; Syafa’at, Ahmad Munib; Mahmudah, Mahmudah (Proceedings of Annual Conference for Muslim Scholars, 2024)
Halal certification is one of the important elements in ensuring product quality and safety, especially for Muslim consumers. This study aims to optimize halal certification assistance for Micro, Small, and Medium Enterprises (MSMEs) products in the Pulau Merah Beach area, Banyuwangi. The research method uses a qualitative approach with data collection techniques through interviews, observations, and documentation studies. Informants in this study consisted of MSME actors in Pulau Merah with interactive model analysis. The results of the study indicate that optimal assistance is needed to increase MSME participation in the halal certification process. An effective assistance program includes ongoing education about the importance of halal certification, providing easier access to information and procedures, and collaboration with the government and related institutions in facilitating certification costs. With the right assistance, MSME products in Pulau Merah Beach can compete in a wider market, including the international market.